Side-lobe level reduction in bio-inspired optical phased-array antennas - Pita, Julián L.; Aldaya, Ivan [UNESP]; Santana, Octávio J. S.; De Araujo, Luís E. E.; Dainese, Paulo; Gabrielli, Lucas H. (Optica Publishing Group, 2017)
Phased arrays are expected to play a critical role in visible and infrared wireless systems. Their improved performance compared to single element antennas finds uses in communications, imaging, and sensing. However, fabrication of photonic antennas and their feeding network require long element separation, leading to the appearance of secondary radiation lobes and, consequently, crosstalk and interference. In this work, we experimentally show that by arranging the elements according to the Fermat’s spiral, the side lobe level (SLL) can be reduced. This reduction is proved in a CMOS-compatible 8-element array, revealing a SLL decrement of 0.9 dB. Arrays with larger numbers of elements and inter-element spacing are demonstrated through a spatial light modulator (SLM) and an SLL drop of 6.9 dB is measured for a 64-element array. The reduced SLL, consequently, makes the proposed approach a promising candidate for applications in which antenna gain, power loss, or information security are key requirements.